Factors associated with engagement and adherence to a low-energy diet to promote 10% weight loss in patients with clinically significant non-alcoholic fatty liver disease. Issue 1 (29th July 2021) - Scragg, Jadine; Hallsworth, Kate; Taylor, Guy; Cassidy, Sophie; Haigh, Laura; Boyle, Marie; Anstee, Quentin; McPherson, Stuart; Avery, Leah
Abstract : Objective: Clinical guidelines recommend weight loss to manage non-alcoholic fatty liver disease (NAFLD). However, the majority of patients find weight loss a significant challenge. We identified factors associated with engagement and adherence to a low-energy diet (LED) as a treatment option for NAFLD. Design: 23 patients with NAFLD enrolled in a LED (~800 kcal/day) were individually interviewed. Transcripts were thematically analysed. Results: 14/23 patients achieved ≥10% weight loss, 18/23 achieved ≥7% weight loss and 19/23 achieved ≥5% weight loss. Six themes were generated from the data. A desire to achieve rapid weight loss to improve liver health and prevent disease progression was the most salient facilitator to engagement. Early and significant weight loss, accountability to clinicians and regular appointments with personalised feedback were facilitators to engagement and adherence. The desire to receive positive reinforcement from a consultant was a frequently reported facilitator to adherence. Practical and emotional support from friends and family members was critically important outside of the clinical setting. Irregular working patterns preventing attendance at appointments was a barrier to adherence and completion of the intervention. Conclusions: Engagement and adherence to a LED in patients with NAFLD were encouraged by early and rapid weight loss, personalised feedback and positive reinforcement in the clinical setting combined with ongoing support from friends and family members. Findings support those identified in patients who completed a LED to achieve type 2 diabetes remission and highlight the importance of behaviour change support during the early stages of a LED to promote adherence.